PEMANFAATAN LIMBAH PERTANIAN TANAMAN PANGAN SEBAGAI PAKAN TERNAK RUMINANSIA DI KECAMATAN WAELATA KABUPATEN BURU - Umaternate, Ani Widya Wati; Eoh, Marna; Patty, Christian Willem (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2023)
Background: This study aims to determine the types of agricultural waste, the use of waste as ruminant feed, and the knowledge of farmers regarding agricultural waste processing. Methods: This research was conducted using survey methods and direct observation in the field. The sampling technique was carried out by purposive sampling, namely three villages (Parbulu, Debowae, and Waelo) based on the highest number of farmers and 30 farmers. Results: This study shows the purpose of raising livestock as a saving 66.67% and the rest as a side business 33.33%. Forage that was given grass and agricultural waste was 76.67% and grass was 23.33%. Utilization of food crop agricultural waste as ruminant animal feed is still low at 23.33%, which provides rice straw agricultural waste in the form of hay as an additional feed and there are 76.67% (23 respondents) who do not know and apply feed processing technology from agricultural waste. Conclusion: The use of agricultural waste of food crops as feed for ruminants in Waelata District, Buru Regency is still very low. This is due to the low level of knowledge and the application of feed processing technology from agricultural waste by farmers/breeders.